Rumah Belajar: The Societal-Based Management of Education - Taufiqurrohman Taufiqurrohman; Achmad Badarudin Latif; Lisnaatul Faundiyah; Desi Astutik (Universitas Islam Nahdlatul Ulama Jepara, 2017)
This article shares an alternative management for holding a non-formal education in the grassroot level of community. Such alternative complement education in Indonesia is commonly what so-called Rumah Belajar (House of Learning). This article parses two samples of it in Jepara. They are managed as well so that it does not reduce the learning quality. It does not only teach hard skill but, more of that, also teach soft skill to the students. It is based on societal benefit in its operation. It does not charge the students with any fees. Instead, it often gives such course equipments to the needy students. The teachers’ spirit of this course is to be beneficial to others. Below is their complete profileKey word: Rumah Belajar, Societal-Based Management, Beneficial Courses